Rede emancipa, movimento social de educação popular, e o currículo escolar : disputas e ocupações no cursinho popular de Pouso Alegre/mg - Visotto, Marcelo Cortez (2023)
The research reported here aimed to increase knowledge about the practices offered by Rede Emancipa, Social Movement of Popular Education, in Pouso Alegre/MG. For this, we seek to understand the importance of the popular education movement in the lives of public education students to access undergraduate courses, as well as student awareness as agents of transformation. One of the central axes of this research is to verify whether student subjectivities produced outside school are recognized by the school curriculum. Below, a brief contextualization of curriculum theories in a scientistic perspective and, in an antagonistic way, the critique of curriculum scientism, based on progressive pedagogy. Through data collection and interviews with coordinators, educators, students and former students of Núcleo Emancipa in Pouso Alegre, an analysis was made of the teaching and student experiences in this popular course and its influences in relation to school education and the curriculum. Among the main results, there is a reconstruction in the symbolic and identity productions of the young people who participated in the popular prep course in Pouso Alegre. In this way, the practice of Emancipa offers science new perspectives for research and the curriculum a redefinition of the teaching-learning process. Two main activities dialogue with the School Curriculum: The Emancipation Circle and Free Time. Such actions made it possible to recognize youth protagonism as pedagogically central in the school environment, announcing, through praxis as action-reflection, a new stage in the historicity of these young people.